Exploring the Consumer Attitude and Current Trends in Automobile Industry with Special Reference to Premium Car Segments: Understanding Consumer Perceptions and Preferences in the Premium Car Segment (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This research paper is about customer perceptions en route for the premium sedan cars in five main market places of Madhya Pradesh. This is based on an approach that has been used for selecting a sedan car on the basis of various car criteria such as Performance, Economy, Comfort, etc. Due to the occurrence of globalization and liberalization, there is stiff completion among the Automobile industries which are focusing attention in capturing the Indian markets an automobile is no longer considered as luxury once, now occupies a part of day-to-day life and has become a necessity. Customers have now changed their attitude that yesterday’s luxuries are today’s necessities. To be a successful marketer it is essential to study the perceptions of prospective buyers and track their drivers of those perceptions.